The involvement of vitamin D in the pathogenesis of anxiety and depression in benign paroxysmal positional vertigo comorbidities - Jinmei Ren; Yuzhu Jiang; Qinghong Zeng; Yang Wang; Qianhong Yang; Yulong Jiang (Traditional Medicine and Modern Medicine)
We review the potential effects and mechanisms of vitamin D (VD) in patients with BPPV-associated anxiety and depression, offering a new perspective for treating the population. Methods: Through a systematic review of existing literature, we analyzed the relationship between VD and comorbid anxiety and depression in BPPV, with a particular focus on neuroendocrine-immune modulation, genetic polymorphisms, oxidative stress, and neuroinflammation. Results: A comprehensive analysis indicates a significant correlation between low levels of VD and the occurrence, recurrence of BPPV, and the comorbid symptoms of anxiety and depression. VD may exert protective effects against BPPV-associated anxiety and depression by regulating neuroendocrine and immune responses, influencing gene expression, and alleviating oxidative stress and neuroinflammation. Conclusion: This review suggests that monitoring VD levels and appropriate supplementation could be crucial for the treatment of patients with BPPV comorbid with anxiety and depression. More research should further validate the specific mechanisms of action of VD and its clinical application value to provide more scientific guidance for the treatment of psychiatric disorders accompanying BPPV.